1998
DOI: 10.1007/s004420050485
|View full text |Cite
|
Sign up to set email alerts
|

Ecological constraints on amphibian metamorphosis: interactions of temperature and larval density with responses to changing food level

Abstract: Phenotypic plasticity is adaptive for an organism inhabiting a variable environment if the optimal phenotype of a trait that affects fitness varies with environmental conditions, and if the organism can perceive environmental conditions and respond appropriately. Wilbur and Collins have proposed that amphibian larvae might respond adaptively to changes in their resource environment. If conditions for growth in the aquatic environment deteriorate, then a tadpole should metamorphose earlier and smaller than a ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
77
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 49 publications
3
77
0
3
Order By: Relevance
“…Temperature and the availability of nutrients have been considered the most important causes in the variation in size and age at metamorphosis (Beck 1997, Alvarez & Nicieza 2002a. Several studies have shown that, among individuals having recently metamorphosed, variation in food availability and diet quality during larval stage can affect the rate of differentiation, the size at metamorphosis and the capacity to escape predators (Travis & Trexler 1986, Beck 1997, Denver 1997, Kupferberg 1997, Newman 1998, Reading & Clarke 1999, Beck & Congdon 2000, Nicieza 2000, Alvarez & Nicieza 2002b, Loman 2002. Due to diets of highest nutritional quality generally produce an increase in the rates of growth and differentiation, it is assumed that the amount of energy and nutrients present in high quality foods would be better utilized by tadpoles.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature and the availability of nutrients have been considered the most important causes in the variation in size and age at metamorphosis (Beck 1997, Alvarez & Nicieza 2002a. Several studies have shown that, among individuals having recently metamorphosed, variation in food availability and diet quality during larval stage can affect the rate of differentiation, the size at metamorphosis and the capacity to escape predators (Travis & Trexler 1986, Beck 1997, Denver 1997, Kupferberg 1997, Newman 1998, Reading & Clarke 1999, Beck & Congdon 2000, Nicieza 2000, Alvarez & Nicieza 2002b, Loman 2002. Due to diets of highest nutritional quality generally produce an increase in the rates of growth and differentiation, it is assumed that the amount of energy and nutrients present in high quality foods would be better utilized by tadpoles.…”
Section: Introductionmentioning
confidence: 99%
“…TH levels reach a maximum during the climax, that is, when the major morphological changes (e.g., tail regression) occur. When environmental parameters (e.g., water volume or food availability) modulate the triggering of metamorphosis, it is always through alteration of the TH production that can thus be viewed as the key endogenous inducer of the metamorphosis process (Boelen et al, 2008;Boorse and Denver, 2003;Denver, 1998;Ito et al, 2004;Newman, 1998;Tata, 2006) (Fig. 2).…”
mentioning
confidence: 99%
“…It has already been reported that densities of conspecific might actually give supplementary information, which individuals can use to 'fine-tune' the timing of their phenotypic transformations (Goldberg et al, 2012). Some authors have proposed changes in habitat, such as pond desiccation, limited food resources, and the presence of predators or competition as mean to affect the duration of the larval stage and the timing of metamorphosis (Newman, 1998). However, we do not throw away the potential of synergetic influence in the setting as a function of relatively stable habitat, where very low seasonal variation in environmental parameters, and no risk of the water body drying up.…”
Section: Discussionmentioning
confidence: 78%